Long‐term Observations Reveal Environmental Conditions and Food Supply Mechanisms at an Arctic Deep‐Sea Sponge Ground. Issue 3 (12th March 2021) - Hanz, Ulrike; Roberts, Emyr Martyn; Duineveld, Gerard; Davies, Andrew; van Haren, Hans; Rapp, Hans Tore; Reichart, Gert‐Jan; Mienis, Furu
Abstract: Deep‐sea sponge grounds are hotspots of benthic biomass and diversity. To date, very limited data exist on the range of environmental conditions in areas containing deep‐sea sponge grounds and which factors are driving their distribution and sustenance. We investigated oceanographic conditions at a deep‐sea sponge ground located on an Arctic Mid‐Ocean Ridge seamount. Hydrodynamic measurements were performed along Conductivity‐Temperature‐Depth transects, and a lander was deployed within the sponge ground that recorded near‐bottom physical properties as well as vertical fluxes of organic matter over an annual cycle. The data demonstrate that the sponge ground is found at water temperatures of −0.5°C to 1°C and is situated at the interface between two water masses at only 0.7° equatorward of the turning point latitude of semi‐diurnal lunar internal tides. Internal waves supported by vertical density stratification interact with the seamount topography and produce turbulent mixing as well as resuspension of organic matter with temporarily very high current speeds up to 0.72 m s −1 . The vertical movement of the water column delivers food and nutrients from water layers above and below toward the sponge ground. Highest organic carbon flux was observed during the summer phytoplankton bloom period, providing fresh organic matter from the surface. The flux of fresh organic matter is unlikely to sustain the carbon demand of this ecosystem. Therefore, the availability of bacteria, nutrients, and dissolved and particulate matter, delivered by tidally forced internal wave turbulence and transport by horizontal mean flows, likely plays an important role in meeting ecosystem‐level food requirements. Plain Language Summary: Sponge grounds are important ecosystems in the deep‐sea that can be compared to tropical reefs. To date, very limited data exist on the range of environmental conditions in areas where deep‐sea sponges and their accompanying fauna are found. In this study, we investigated environmental conditions at a deep‐sea sponge ground located on the summit of an Arctic seamount. Measurements of the water around the seamount and close to the sponge ground were performed recording near‐bottom physical properties as well as the food supply over an annual cycle. At the summit of the seamount, the water flow interacts with the seamount itself, which produces turbulent mixing with temporarily high current speeds. At the same time, water movements around the seamount deliver food and nutrients from water layers above and below toward the sponge ground. Fresh food from the surface water was delivered only during one major event in the summer phytoplankton bloom period. The amount of food sinking from the surface is unlikely to sustain the energetic demands of this ecosystem. Therefore, the availability of other food resources such as bacteria, dissolved and particulate matter and their delivery by water movements likely play an important role in meeting ecosystem‐level food requirements. Key Points: Long‐term study at a deep‐sea sponge ground provides environmental ranges known to support sponges Hydrodynamic processes deliver water with different beneficial characteristics from above and below toward the sponge ground Benthic organisms receive only a small amount of food sinking from the surface waters, which is likely not sustaining their energy demand